2021
DOI: 10.21067/jpm.v6i2.5548
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kompetensi Guru SLB Negeri Bugih Pamekasan Melalui Pemanfaatan Media Pembelajaran dan Aplikasi Belajar Online

Abstract: The conditions of the Covid-19 pandemic caused extraordinary changes in various sectors of life, including in the education sector. The closure of all school institutions "forced" the teachers transform their learning into online learning to reduce the potential spread of the Corona Virus in one school environment. Unfortunately, it had been a year after the implementation of learning from home began; the challenges and obstacles in implementing online learning were still felt at SLB Negeri Bugih Pamekasan. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Assistance for the use of digital media in science learning has not been done much so far. Similar service activities have been carried out previously by Ramadani et al (2021) to support the learning process during the pandemic, while Isnainiyah et al (2022) also reported on activities to empower special school teachers in utilizing Google Assistant-based media. Meanwhile, mobile application-based training for early childhood teachers is reported to be able to create innovative learning media as a means of supporting their teaching (Noviar et al, 2023).…”
Section: Introductionmentioning
confidence: 69%
“…Assistance for the use of digital media in science learning has not been done much so far. Similar service activities have been carried out previously by Ramadani et al (2021) to support the learning process during the pandemic, while Isnainiyah et al (2022) also reported on activities to empower special school teachers in utilizing Google Assistant-based media. Meanwhile, mobile application-based training for early childhood teachers is reported to be able to create innovative learning media as a means of supporting their teaching (Noviar et al, 2023).…”
Section: Introductionmentioning
confidence: 69%
“…Students are very enthusiastic in participating in the lesson, when the teacher asks several questions and invites students to draw conclusions from the material that has been learned, students are more active in responding to questions and case illustrations given by the teacher. Students who often practice questions or get practice questions will have better thinking skills (Ibam et al, 2018;Kusuma et al, 2017;Ramadani et al, 2021). Students who are accustomed or trained to hone skills in thinking, it will be easier to digest and understand a material.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is necessary to make efforts to improve and form effective teaching strategies for students with special needs (de Boer et al, 2011;Rosita & Suherman, 2020;Shaukat et al, 2019). Keeping up with the dynamic times, and the rapid increase in the field of technology also demands the ability of teachers to continue to improve and update skills, including skills in developing teaching innovations with digital-based media utilization (Ramadani et al, 2021;Soetan et al, 2021). To provide multimedia-based learning for children with special needs, an understanding of the conditions of each student is required.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research findings stated that the use of appropriate learning media can help students learn so that it has an impact on increasing student understanding (Evianti & Atika, 2021;Fitriyana et al, 2020;Kusumawati et al, 2017;Ramadani et al, 2021;F. Wulandari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%